‘MAIN TERI’ TRADITIONAL HEALING STILL WIDELY SOUGHT-AFTER - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 3 February 2016 – Traditional healing or Main Teri performed by traditional healers called Tok Teri is still much sought after by those seeking alternatives to modern treatment.